PPARy Expression in Eutopic and Ectopic Endometrium of Reproductive Age Women with Endometriosis - Adya F Dilmy; Muharam Natadisastra; Kanadi Sumapradja (Indonesian Journal of Obstetrics and Gynecology, 2015)
Objective: To evaluate the expression of PPARy receptor and to compare its expression in eutopic and ectopic endometrium in women with endometriosis. Method: This is a cross sectional study. Ten female subjects with endometriosis that underwent laparoscopy or laparotomy who fulfilled the inclusion criteria were recruited by consecutive sampling. Two samples were taken, eutopic endometrium and ectopic endometrium from endometriosis cyst wall during surgery of each subject. PPARy expression was examined by two-step RT-qPCR. Our data was statistically examined using the paired t-test and Pearson’s correlation test. Result: PPARy was found to be expressed in eutopic and ectopic endometrium of women with endometriosis using the RT-qPCR method. The expression of PPARy was not statistically different in eutopic and ectopic endometrium (1.16 relative fold vs 1.25 relative fold; p=0.26). By Pearson’s correlation there was a weak positive correlation between PPARy expression of eutopic and ectopic endometrium (r=0.16). Conclusion: PPARy was detected by two-step RT-qPCR in eutopic and ectopic endometrium of women with endometriosis. Semiquantification of PPARy expression showed that there was no significant difference between PPARy expression in eutopic and ectopic endometrium of women with endometriosis. There was a weak positive correlation between PPARy expression in eutopic and ectopic endometrium of women with endometriosis. [Indones J Obstet Gynecol 2015; 3-4: 200-205] Keywords: endometriosis, PPARy, two-step RT-qPCR